Development of new logo design method for startup brands - M Johari, Mariah (2019)
A lot of people tend to underestimate the importance of typography when it comes to logo design. It has been proven that typography could provide certain impressions to the psychology and cognitive thoughts. However, there are less research-based rules to guide designing or interpreting typographic meaning in logo design that affect consumers’ perceptions. Thus, this research describes consumers’ emotions in evaluating logo appearance towards selection of typography physical categories and logo design element to bold the brand. The literature has documented methods that are commonly used to integrate the typography used in logo design element with consumers’ emotions involved for startup brands. The measurement of emotions is determined by eight (8) basic emotion approaches. The studies aim to provide guidelines and understanding on how use of typography can produce different emotion responses for logo design and reflect towards consumers’ perceptions. A guideline used to present the analysis of consumers’ emotions in relation to the designers’ environment that involved in the logo design process. This research establish to develop new logo design specifications guidelines and as well as to increase the recognitions in the market. This research study was also bears the hopes in benefiting the marketers, advertisers and designers in developing new logo design for startup brands.